Graph-directed random fractal interpolation function - SOMOGYI, Ildikó; SOÓS, Anna (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
Barnsley introduced in [1] the notion of fractal interpolation function (FIF). He said that a fractal function is a (FIF) if it possess some interpolation properties. It has the advantage that it can be also combined with the classical methods or real data interpolation. Hutchinson and Ruschendorf [7] gave the stochastic version of fractal interpolation function. In order to obtain fractal interpolation functions with more exibility, Wang and Yu [9] used instead of a constant scaling parameter a variable vertical scaling factor. Also the notion of fractal interpolation can be generalized to the graph-directed case introduced by Deniz and Ozdemir in [5]. In this paper we study the case of a stochastic fractal interpolation function with graph-directed fractal function. Mathematics Subject Classification (2010): 28A80, 60G18.